The quantum cell - Torday, John S. (Progress in biophysics and molecular biology, 2024)
There is a consensus that we are conscious of something greater than ourselves, as if we are derived from some other primordial set of principles. Classical or Newtonian physics is based on the Laws of Nature. Conversely, in a recent series of articles, it has been hypothesized that the cell was formed from lipid molecules submerged in the primordial ocean that covered the earth 100 million years after it formed. Since lipids are amphiphiles, with both a positively- and negatively-charged pole, the negatively-charged pole is miscible in water. Under the influence of earth's gravity, the lipid molecules stand up perpendicularly to the surface of the water, packing together until the negative charge neutralizes the Van der Waals force for surface tension, causing the lipid molecules to ‘leap’ into the micellar form as a sphere with a semi-permeable membrane. Particles in the water freely enter and exit such spheres based on mass action. Over time such protocells evolved Symbiogenesis, encountering factors that posed existential threats, assimilating them to form physiology to maintain homeostatic control. Importantly, when differentiated lung or bone cells are exposed to zero gravity, they lose their phenotypic identity in their evolved state, which has been interpreted as transiting from local to non-local consciousness.